Evaluasi Daya Dukung dan Skenario Konservasi DAS Wosi di Kabupaten Manokwari, Papua Barat - Mahmud Mahmud; Danang Wijaya; Wahyudi Wahyudi; Ambar Kusumandari (Jurnal Ilmu Kehutanan, 2021)
Around 12.62% of watersheds in Indonesia are damaged and need restoration immediately to prevent floods, landslides, and other related disasters. This study aimed to evaluate the Wosi watershed and formulate conservation scenarios to improve its conditions. The data collection included hydrology (quantity, continuity, and water quality), land (critical land index, percentage of vegetation cover, and erosion index), socio-economic (population pressure, welfare level, existence, and regulations enforcement), building investment (city classification and water building value classification), and the use of space (protected areas and cultivation areas). The evaluation of carrying capacity used a scoring analysis. The scenarios formulation used the information on potential carrying capacity and conservation strategies. The results suggested that the carrying capacity of the Wosi watershed from 2016-2019 had fallen into "bad" and "very bad" categories. To improve these conditions, the government can assign the riparian areas as a government asset, build ponds and dikes in the flood-prone areas, apply small recharge pond (SRP) on the cacao plantations, and assign Wosi Rendani protected forest (HLWR) as an urban forest. The implementation of these conservation strategies will result in the improvement of (a) the carrying capacity of the Wosi watershed and (b) the status into the "good" category to support environmentally friendly development in Manokwari city.